Western Apache NT21 (eHRAF World Cultures, 2002)
This file contains 48 documents that deal with the White Mountain, Cibecue, and San Carlos Apache Native Americans living for the most part on the Fort Apache and San Carlos Indian reservations in Arizona. The focus is divided between the traditional Western Apache culture of the Pre-Reservation period, and the Post-Reservation period